The Effect of Financial Performance on the Profitability to Coal Mining Company Subsectors in Indonesia Stock Exchange - Siti Asma Fauziyah; Said Djamaluddin (Syntax Corporation Indonesia, 2021)
This study aims to determine the effect of financial performance on profitability in coal companies, the period 2014-2019. This study uses a panel data regression method with a Fixed Effect Model research model approach where samples of 19 companies with populations of 26 in the Coal Sub-sector companies are obtained according to the criteria set by the author based on observations for 6 years, namely 2014-2019 using the E-views program 10 and Microsoft Excel 2016. The result shows that partially the variable Net Working Capital, Firm Size, Current Ratio, Debt to Equity Ratio, and Total Assets Turnover influence Return On Assets. The variables of Net Working Capital, Firm Size, Debt to Equity Ratio have a negative relationship, while the variables Current Ratio and Total Assets Turnover have a positive relationship. In coal mining companies listed on the Indonesia Stock Exchange in 2014-2019.